(untitled) (Indian Journal of Arid Horticulture, 2025)
Fifteen landraces of sponge gourd were evaluated for 19 quantitative characters to study the genetic variability and association of the traits. The analysis of variance revealed considerable genetic variability in the evaluated germplasm. The GCV and PCV estimates were high for fruit yield/plant, number of fruits/plant and number of seeds/fruit indicating better scope for improvement through simple selection. These characters also depicted high estimates for heritability and genetic gain indicating additive type of gene action. Fruit yield/plant showed positive and significant association with number of fruits/plant and fruit weight. Among the genotypes tested for performance studies, AHSG-4 and AHSG-5 recorded the highest fruit yield potential under arid conditions. The genotype AHSG-4 exhibited earliness (53.84 days) for first marketable harvest.